EXPLORING INDONESIAN EFL WRITING ERRORS: INSIGHTS FROM THE STIFIN PERSPECTIVE - Benni Ichsanda Rahman Hz; Soraya Grabiella Dinamika (ELT Echo : The Journal of English Language Teaching in Foreign Language Context, 2024)
This study aims to investigate the writing errors made by EFL students based on their brain dominance machine: Sensing, Thinking, Intuiting, Feeling, and Instinct (STIFIn). A qualitative case study was adopted in finishing this study. The data collected in this study were processed by using two methods: statistical calculations for quantitative data about the errors the participants made in their text writing by using Gass & Selinker’s (2008) writing errors approach which was then categorized based on the respondents’ STIFIn brain dominance, and constructive analysis for qualitative data related to the results of comparing the errors. This study enrolled 41 students from a college of management studies, located in the city of Medan, Indonesia. The individuals with Sensing Extrovert made the most errors, with a ratio of 1:15 errors recorded in their texts, followed by Intuiting Introvert with 1:14,5 errors, Thinking Extrovert with 1:13,3 errors, and Thinking Introvert with 1:13 errors. Sensing Introvert made 1:12,5 errors, Instring 1:9,4, Intuiting Extrovert 1:9, Feeling Introvert 1:7,6, and Feeling Extrovert 1:7,5. Sensing Extrovert students committed the most errors, whereas Feelings (extrovert and introvert) produced the fewest. Numerous of the causes behind these results are discussed in detailed explanation within the STIFIn theory.